The Rivera Condom in the Management of Complicated Open Abdomen: A Case Report - Julio Cesar Ortega Maria; Flávio Antônio de Sá Ribeiro; Luis Fernández de Córdova Rio de la Loza (International Journal of Medical Science and Clinical Research Studies, 2026)
The hostile abdomen represents one of the most challenging scenarios in general surgery and is characterized by loss of normal anatomical planes, dense adhesions, persistent inflammation, and fibrosis, generally secondary to infectious processes, multiple surgical interventions, or severe abdominal complications. The development of intestinal fistulas in the setting of an open abdomen considerably increases morbidity and mortality due to continuous wound contamination, fluid and electrolyte losses, nutritional deterioration, and the risk of sepsis. The Rivera condom technique represents an alternative approach for the isolation and drainage of intestinal effluent in patients with fistulas and a complex abdomen. We present the case of a 15-year-old male patient with a history of complicated appendicitis who, following surgical treatment and subsequent abdominal complications, developed a hostile abdomen associated with intestinal fistulas. Because of the severe inflammatory response, extensive adhesions, and loss of normal anatomical planes, further surgical intervention posed a high risk of visceral injury and the development of additional fistulas. Given the difficulty in controlling the intestinal effluent, the Rivera condom technique was used, with the devices positioned over the fistulous openings to isolate and direct the effluent externally, thereby reducing its contact with the wound surface and facilitating local management of the open abdomen. Control of intestinal effluent is one of the fundamental principles in the management of fistulas associated with a hostile abdomen and should be integrated into a multidisciplinary approach that includes sepsis control, fluid and electrolyte replacement, nutritional support, tissue protection, and planning for eventual definitive reconstruction. The Rivera condom technique represents a simple, adaptable, and low-cost alternative that enables individual isolation of fistulous openings and controlled drainage of intestinal contents, particularly when wound characteristics limit the use of conventional devices. In the present case, this technique provided adequate isolation of intestinal effluent in an adolescent patient with a complicated open abdomen following appendicitis, representing a useful tool within the staged management of a highly complex surgical condition.